SUN-LB77 Incidental Anaplastic Thyroid Carcinoma: An Uncommon Entity - Padmanaban, Preethi (J Endocr Soc, 2020)
Background: Anaplastic thyroid cancer is an aggressive thyroid malignancy with a median survival of 3 to 9 months. It is rare and represents 2-5% of all thyroid tumors. Even more uncommonly in about 2%–6% of all ATC cases, it is identified as a small, incidental finding after surgical resection of a predominantly non-anaplastic tumor. Clinical Case: We report a case of 67 year old Caucasian male who presented with history of hoarseness of voice for one month. Fine needle aspiration biopsy of right dominant thyroid nodule revealed papillary thyroid cancer. Pre-operative imaging was negative for involvement of surrounding structures or distant metastasis. He underwent total thyroidectomy and final pathology revealed Anaplastic carcinoma arising in papillary carcinoma measuring 3.6cm in greatest dimension. Undifferentiated (Anaplastic) Carcinoma comprised approximately 5% of the tumor. Areas from anaplastic and papillary tumor were dissected separately. DNA separated from these two specimens were analyzed by PCR amplification and both were positive for BRAF mutation. External beam radiation and radioactive iodine therapy were administered after surgery. Given absence of invasion or metastasis adjuvant therapy was not initiated. His positron emission tomography, computed tomography imaging and whole-body scan has been negative for residual/ recurrent or metastatic disease. He remains disease free at 18 months after diagnosis. Discussion: Anaplastic thyroid cancer is a rare but highly aggressive tumor. In most cases it develops from a pre-existing well differentiated thyroid cancer. ATC incidence typically peaks at the 6-7th decade of life, predominantly in women. The median survival is between 3 to 9 months with less than 10% of patients alive 3 years after the time of diagnosis. Because of its aggressive behavior, the American Joint Committee on Cancer Staging Manual classifies all Anaplastic thyroid cancer Stage IV tumors. Surgery, chemotherapy and radiotherapy are the conventional therapeutic strategies performed in the attempt to improve survival. However, incidental anaplastic thyroid cancer is rare variant with very few reported cases. American Thyroid Association (ATA) Guidelines for Management of Patients with ATC do not include specific recommendations for this form of ATC. There is no consensus to define best treatment approach as to whether intrathyroidal incidentally detected ATC is best treated with surgery alone, surgery followed by radiotherapy, or surgery followed by chemotherapy plus radiation therapy. Conclusion: Based on review of our case as well as outcomes of similar reported cases, prognosis is favorable for incidental anaplastic thyroid cancer. Hopefully, with more data from similar cases to demonstrate difference in disease free survival we should be able to define the role of chemotherapy and adjuvant therapy for incidental ATC better. The question remains open, as to whether incidental anaplastic thyroid cancer should be considered as a separate entity from aggressive form of ATC.